Produtividade e complexidade econômica: uma análise do caso brasileiro - Aragão, Roberto Barbosa de Andrade (2016)
In the context of economic development, this study has as its main objective to explorer the relationship between international trade and productivity. After making a wide review on theories of international trade and theories of economic development, we seek to determine the causal relationship between these two variables. The question that follows refers to the direction of causality, i.e., productivity, generates international trade or international trade generates productivity? This work suggests that both directions are possible and the difference is just in the productivity component being analyzed. Thus, productivity at the product level (structural) generates trade, as argued Smith (1776) and Ricardo (1817), but trade generates productivity (within) as argued Hausmann, Hwang and Rodrik (2007) and McMillan and Rodrik (2011). Further, the study makes a comprehensive analysis of the methods of decomposition of productivity, concluding that there is more than one way of doing this decomposition and the interpretation of each of these approaches differ and may bias the findings. In addition, the decomposition of productivity is made in its components in two distinct databases: 10-Sector Database of GGDC and national accounts of IBGE, concluding that, depending on the base, the results can vary significantly. Similarly, within a structuralist approach, this research differentiate sectors that have the greatest growth potential from traditional sectors with lower growth potential. Defining the complexity of exports as the concept developed by Hausmann at al (2014), this investigation estimates using Brazilian data, through a dynamic panel model, the coefficients of a suggested equation to explain variations in the static structural productivity effect. The estimated model suggests that the complexity of exports significantly and positively affects the structural component of productivity. Thus, it can be said that exports of more sophisticated products boosts productivity through its structural component.